Inter-partner Credible Threat in International Joint Ventures: An Infinitely Repeated Prisoner's Dilemma Model - Zhang, Yan; Rajagopalan, Nandini (Journal of International Business Studies, 2002)
We use an infinitely repeated prisoner's dilemma model to examine the role of inter-partner credible threat in international joint ventures (IJVs). Inter-partner credible threat refers to the certainty of either partner's retaliation given the other partner's earlier cheating. We argue that inter-partner credible threat represents the first order determinant and partners’ management control represents the second order determinant of partner payoffs. When inter-partner credible threat is present, both partners achieve balanced payoffs whereas when it is absent, partners’ relative control will determine their relative payoffs. In-depth interview data from four IJVs in China provide preliminary support for our theoretical arguments.